STRATEGI PROMOSI ON-AIR PROGRAM GARUDA MELALUI AKUN MEDIA SOSIAL INSTAGRAM - Rangga Permana; Syifa Amatillah (PT. RANESS MEDIA RANCAGE, 2024)
Rapid technological advancements influence how humans communicate and socialise, including through social media platforms such as Instagram. Instagram, which offers photo and video sharing tools, is becoming more accessible as technology and smart device capabilities progress. Television, being a mass medium, must adapt to the existence of digital media. NET., a private television channel, uses social media to attract viewers and promote its programmes. Instagram is used as an on-air promotional medium by Garuda's NET. television programme. This documentary tries to instill love for the country by highlighting the humanitarian aspect and pride to the Indonesian National Army (TNI). The goal of this research is to determine the Garuda program's promotional strategy and purpose for using Instagram, and it employs qualitative descriptive methods such as observation, interviews, and recording. According to the research findings, the on-air promotion strategy is carried out in stages, including composing scripts for social media material, seeking and editing photo and video content, and content approval by reporters. After this stage, the content is posted at the given time frame. Since November 28, 2016, the Garuda programme has actively used Instagram to promote its programme. The @garuda_net account is used to convey information about the TNI, including leaks and bits of coverage from reporters' live actions, which boosts soldiers' enthusiasm and cooperation while shooting. This account also serves as a platform for interaction and information gathering from Instagram followers who are dedicated to military and TNI material, particularly Garuda viewers.